Down-regulation of let-7a-5p predicts lymph node metastasis and prognosis in colorectal cancer: Implications for chemotherapy. (December 2016) - Liu, Tsang-Pai; Huang, Chi-Chou; Yeh, Ken-Tu; Ke, Tao-Wei; Wei, Po-Li; Yang, Ji-Rui; Cheng, Ya-Wen
Abstract: Colorectal cancer (CRC) guidelines recommend adjuvant chemotherapy according to the level of lymph node metastasis. Let-7a-5p is a microRNA, which inhibits migration, invasion, as well as the epithelial-mesenchymal transition by targeting HMGA2 . The aim of this study was to investigate the role of let-7a-5p in the clinical impact of CRC. In this study, one hundred and ninety-two CRC patients were enrolled. The expression of let-7a-5p and HMGA2 in serum and tumour tissues were analysed by real-time PCR and immunohistochemistry. Kaplan–Meier analysis was used to analyse primary outcomes, including the survival and tumour recurrence. The expression of let-7a-5p in tumour tissues was significantly negative correlated with the tumour size, stage and lymph node metastasis in CRC patients ( p = 0.024 for tumour size, p < 0.0001 for stage and p < 0.0001 for lymph node metastasis). There was a negative correlation between the levels of let-7a-5p and the HMGA2 protein ( p < 0.0001). The overall survival (OS) and disease-free survival (DFS) rates of patients with let-7a-5p low/ HMGA2 high were poorer than those with let-7a-5p high/ HMGA2 high, let-7a-5p high/HMGA2 low and let-7a-5p low/ HMGA2 low. In addition, the expression levels of let-7a-5p in serums were positively correlated with let-7a-5p in the tumour tissues of the CRC patients. The expression levels of let-7a-5p in serums also could be used as a biomarker to predict clinical outcome. We suggest that down-regulation of let-7a-5p in serums and tumour tissues of CRC patients could be used to predict lymph node metastasis and the disease prognosis. These results could be implicated for chemotherapy suggestion. Highlights: Let-7a-5p expression levels of CRC patients were negatively correlated with metastasis. Let-7a-5p and HMGA2 could be used to predict clinical outcomes and tumour recurrence in CRC. Let-7a-5p in tumour tissues and serum might be used as biomarkers to recommend chemotherapy in CRC.